Synthesis, characterisation and biological activities of 2-Methylbenzyl 2-(dipyridin-2-yl methylene) hydrazinecarbodithioate. - Ravoof, Thahira Begum S A; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim; Rosli, Rozita; Watkin, David John; How, Fiona Ni Foong (Springer, 2011)
A new tridentate nitrogen–sulphur Schiff base has been synthesised from the condensation of di-2-pyridylketone and a novel dithiocarbazate, S-2-methylbenzyl-dithiocarbazate (S2MBDTC). The Schiff base was characterized using various physico-chemical and spectroscopic techniques. The X-ray crystallographic analysis of the Schiff base is reported. The Schiff base crystallized in a monoclinic system with a space group of P 21/n, with crystal cell parameters a = 10.8128 (2) Å, b = 9.3832 (2) Å, c = 18.0352 (4) Å, β = 97.1311 (9)°. The Schiff base was found to be inactive against selected microbes and two breast cancer cell lines (MCF-7 = Human breast cancer cell line with positive estrogen receptor and MDA-MB-231 = Human breast cancer cell line with negative estrogen receptor).